Rhetorical Precision in Educational Leadership: Optimizing Policy Communication for Effective Governance - Vincent Oringo; Rifkah Fitriyah; Hari Adi Rahmad; Fadli Surahman (Universitas PGRI Sumatera Barat, 2024)
This study investigates the rhetorical strategies used by a leadership university in a policy speech, focusing on the communication of leadership strategies within an academic context. Through a discourse analysis approach, the research explores how the message is organized, delivered, and perceived by audiences on social media platforms. The findings reveal that while the speech addresses critical issues related to educational leadership and policy, its effectiveness is diminished by excessive repetition, convoluted sentence structures, and poorly timed pauses that disrupt the speech's flow. Despite the relevance of the topics, these communication flaws reduce the clarity and impact of the core messages on educational administration and policy outcomes. The study also examines how rhetorical choices, such as specific word selection and speech structure, either enhance or undermine the speaker’s goals. These insights underscore the necessity for clear, concise, and well-structured communication in educational leadership, particularly when dealing with complex policy matters. This research offers valuable contributions to the field of educational governance, providing practical recommendations for refining leadership communication to improve the reception and implementation of policy initiatives.